2015
DOI: 10.1042/bj20140872
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin-dependent actin bundling regulates cell migration and traction forces

Abstract: Vinculin binding to actin filaments is thought to be critical for force transduction within a cell, but direct experimental evidence to support this conclusion has been limited . In this study, we found mutation (R1049E) of the vinculin tail impairs its ability to bind F-actin, stimulate actin polymerization, and bundle F-actin in vitro. Further , mutant (R1049E) vinculin expressing cells are altered in cell migration, which is accompanied by changes in cell adhesion, cell spreading, and cell generation of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 33 publications
1
44
1
Order By: Relevance
“…2b), suggesting that both regions of the protein contribute to the density and engage the actin surface. This conformation of the C-terminus is consistent with the recent report that R1049 is important for actin binding 29 , bringing this residue close to the negatively charged surface of subdomain 2 (Fig. 2c).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2b), suggesting that both regions of the protein contribute to the density and engage the actin surface. This conformation of the C-terminus is consistent with the recent report that R1049 is important for actin binding 29 , bringing this residue close to the negatively charged surface of subdomain 2 (Fig. 2c).…”
Section: Resultssupporting
confidence: 92%
“…Both activities are required for vinculin function in vivo, as lesions that selectively disrupt them in the context of the full-length molecule lead to defects in cell spreading, adhesion formation and maturation, and mechanotransduction 6; 27; 28; 29 . Cross-linking and tomographic studies indicate that actin bundling occurs through oligomerization of the Vt domain 26; 27; 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The different effects of actin binding on the cell areas at physiological levels of stiffness and on extremely rigid substrates have also been reported [35]. One possibility to explain the discrepancy between the effects on the physiological levels of stiffness (gel substrates) and extremely rigid (glass) substrates is as follows: two tensile forces transmitted from two actin-binding surfaces are required for activation and CSB resistance of vinculin on the physiological level of stiffness because of the weak intracellular tension, while a high tensile force transmitted from one actin-binding surface on extremely rigid substrates is enough for them.…”
Section: Discussionmentioning
confidence: 99%
“…They predicted F-actin binds two distinct surfaces in the vinculin tail: an upper (amino acids 925–952) and lower monomer site (amino acids 1050–1056) [15]. Experimental data from four groups, including our laboratory, support residues or regions identified by Janssen are important for the interaction between vinculin and actin [13, 15, 59, 60]. However, other studies revealed that mutation of residues outside the upper and lower monomer perturb actin binding to vinculin [46, 58].…”
Section: Vinculin In Cell–matrix Adhesionsmentioning
confidence: 99%